Food antibodies in oral disease: A study of serum antibodies to food proteins in aphthous ulceration and other oral diseases. Issue 5 (May 1973) - Thomas, H. C.; Ferguson, Anne; McLennan, J. G.; Mason, D. K.
Abstract : We have investigated the incidence of antibodies to food antigens in patients with recurrent minor aphthous ulceration and in patients with other oral ulcerative diseases. The incidence of these antibodies was the same in both groups of patients and was significantly greater than the incidence in a control group of normal people. There was no evidence to support the hypothesis that aphthous ulceration is primarily due to hypersensitivity to food antigens. The factors which might contribute to the absorption of antigenic molecules from the mouth and to the increased immune response in patients with oral disease have been considered.